The argument-as metaphor in decision-making visualisation - McGinn, J.; Picking, R. (Information visualization : proceedings : Seventh International Conference on Information Visualization : an international conferenece on computer visualization & graphics applications : 16-18 July, 2003, London, England, 2003)
We describe 'argument-as' metaphors and how they may be used as a vehicle to visualise decision support information. We argue that our approach is particularly useful for users who may not have advanced computing skills, and who have little time to dedicate to in-depth analysis of the information. We present an interface which, as a result of using an argument-as metaphorical approach, is simple to understand, easy to manipulate, and transparent in its display of underlying reasoning.